Determining the interphase thickness and properties in carbon fiber reinforced fast and conventional curing epoxy matrix composites using peak force atomic force microscopy. (10th November 2019) - Qi, Yixin; Jiang, Dazhi; Ju, Su; Zhang, Jianwei; Cui, Xin
Abstract: Quantitative analyses of the thickness and properties of the interphase in carbon fiber reinforced resin matrix composites, which play an important role in loading transfer, are essential and intuitive to accurately design the properties of the composites. In this study, to know the distinctions of the interphase between the carbon fiber reinforced fast and conventional curing epoxy matrix composites quantitatively and completely, in addition to modulus map, adhesion map by Peak Force Quantitative Nano-Mechanics technology was newly introduced and applied to determine the interphase thickness and properties. The interphase in the fast curing epoxy matrix composites in modulus image was found to be soft with an average thickness of 20.03 ± 2.04 nm, while it was 40.48 ± 4.17 nm in the conventional curing epoxy matrix composites, and the modulus of the interphase formed a depression between the fiber and the matrix. Consistent with the interphase thickness determined by the modulus, the average interphase thickness in the fast and conventional curing epoxy matrix composites were 19.45 ± 0.68 nm and 41.01 ± 3.98 nm, respectively, based on the adhesion contrast in the interphase, and the adhesion of the interphase reached a peak between the fiber and the matrix. Compared with the conventional curing epoxy matrix composites, the modulus and the adhesion of the interphase changed more sharply in the fast curing epoxy matrix composites. Obviously, numerous distinctions of the interfacial properties existed between the fast and conventional curing epoxy matrix composites.